The Development of Spatial Representation Through Teaching Block-Building in Kindergartners - Cai, Liman; Luo, Jiutong; Zhang, Hui; Ying, Jinling (Frontiers in Psychology, 2020)
This study investigated the effects of the teaching block-building intervention on overall spatial representation and its three sub-forms, namely linguistic, graphic and model representations, in kindergartners. Eighty-four children (39 girls and 45 boys), aged 5-6 years old, were randomly selected and equally divided into two groups, i.e., experimental group and control group. The experimental group received the intervention of teaching block-building for 14 weeks (45 minutes each time, once a week), while children in the control group freely played with blocks for the equivalent time. Children’s spatial representation performances were measured in both pre- and post-tests by the Experimental Tasks of Spatial Representation for Children. The results showed that: (1) teaching block-building could promote not only the overall spatial representation but also all three sub-forms of spatial representations; (2) there was no gender differences regarding the effect of teaching block-building on neither the overall nor three sub-forms of spatial representations; (3) after the intervention, the diversity of children’s choices regarding the use of sub-forms spatial representations was also promoted in the experimental group. In summary, these results contributed to a comprehensive and systematic understanding of the effects of teaching block-building on spatial representation among children in kindergartens.